As representações de Getúlio Vargas nas páginas da Revista do Globo (1929-1937): de gaúcho a chefe da nação - Araújo, Eduardo Barreto de (2015)
This work is linked to the Graduate Program in History at the Federal University of Santa Maria and inserted into the Research Line Integration, Politics and Frontier. We present and analyze the representations of Getúlio Vargas in the pages of the magazine Revista do Globo between the years 1929 until 1937, and to present the magazine as the largest vehicle of Rio Grande do Sul state information within your style. We also tried to present an analysis of the image of Getulio Vargas unrelated to the primacy given to the Departamento de Imprensa e Propaganda and present the use of his image in a period prior to that traditionally elects historiography. Therefore, we elected methodologically the image as a source for the historian, recognizing it as a bearer of memory, as well as to represent the past.